(untitled) (Fiep Bulletin - online, 2013)
The treatment done out in pool therapy, provides many positive effects. Specifically individuals with spinal cord injury in the hydrotherapy has great therapeutic value as regards the reduction of spasticity and contractures through heated water. In addition to reducing the pain and muscle spasms, maintain or increase the range of motion, muscle rehabilitation, stretching and muscle strengthening, encouragement of functional activities, maintenance and improvement of balance, coordination and posture, respiratory infections, increase in life expectancy, increased levels of integration, aid in fighting the disability, fostering independence, improved self-image, self-esteem and satisfaction with life, among others. This study aimed to measure and quantify answers related to muscle strength of trunk after physiotherapeutic treatment of different approaches, contributing to new forms of intervention in physiotherapy neurofuncionnal. Part of this research two male patients diagnosed with spinal cord injury at chest level, the ages of 28 and 40 years. Assessment was used as the measurement of muscle strength of the trunk dynamometer Crown, and made an assessment at the beginning and one at the end of treatment, totaling 12 attendants. One patient received treatment hydrotherapeutic associated with therapy and other neurofuncionnal only therapy neurofuncionnal. The results were achieved through graphs with the Excel database, and simple percentage. From the results, there was a positive response in the two treatments, but it was felt best results when related to the treatment hydrotherapy.